2018
DOI: 10.21833/ijaas.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyberloafing on employee productivity

Abstract: The aim of this paper is to explore the cyberloafing behavior and its effect on employees' productivity. A total of 250 employees were asked to participate in a survey of 20 companies in Saudi Arabia, in which a controlled experiment was conducted to collect and analyze data. From the results, the odds of a person spending zero hours using the internet were seen to be more productive. An increase of 1 hour using the internet for educational activity will increase the odds of being productive by three times. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Some studies found that cyberloafing negatively affects productivity at work (Buyruk Akbaba, 2019;Demir, Ürek & Uğurluoğlu, 2017;Hussain & Parida, 2017;Jiang, 2020;Kuschnaroff & Bayma, 2014;Lim, Teo, & Loo, 2002;Mercado, Giordano & Dilchert, 2017;Shaddiq, Haryono, Muafı & Isfianadewi, 2021). On the other hand, some studies found the opposite, namely stating that the effect of cyberloafing on productivity at work is positive (Blanchard & Henle, 2008;Keklik, Kılıç, Yıldız H., & Yıldız, B., 2015;Koay ve Soh, 2018;Saleh, Daqqa, Abdulrahim, & Sakallah, 2018;Sao, Chandak, Patel & Bhadade, 2020;Weissenfeld, Abramova & Krasnova, 2019). In this context, the lack of a significant relationship between the two variables can be linked to a lack of clear consensus in the literature.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that cyberloafing negatively affects productivity at work (Buyruk Akbaba, 2019;Demir, Ürek & Uğurluoğlu, 2017;Hussain & Parida, 2017;Jiang, 2020;Kuschnaroff & Bayma, 2014;Lim, Teo, & Loo, 2002;Mercado, Giordano & Dilchert, 2017;Shaddiq, Haryono, Muafı & Isfianadewi, 2021). On the other hand, some studies found the opposite, namely stating that the effect of cyberloafing on productivity at work is positive (Blanchard & Henle, 2008;Keklik, Kılıç, Yıldız H., & Yıldız, B., 2015;Koay ve Soh, 2018;Saleh, Daqqa, Abdulrahim, & Sakallah, 2018;Sao, Chandak, Patel & Bhadade, 2020;Weissenfeld, Abramova & Krasnova, 2019). In this context, the lack of a significant relationship between the two variables can be linked to a lack of clear consensus in the literature.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 99%
“…Keklik, Kılıç, Yıldız H., ve Yıldız, B., 2015;Koay ve Soh, ,2018;Saleh, Daqqa, Abdulrahim, ve Sakallah, 2018;Sao, Chandak, Patel ve Bhadade, 2020;Weissenfeld, Abramova ve Krasnova, 2019). Bu bağlamda, banka çalışanlarının sanal kaytarma yaptıkları zamanlarda sanal kaytarmanın bütünüyle olumsuz sonuçları ile karşılaşmadıkları, aksine iş ortamından uzaklaşma, zihinsel olarak dinlenme, bilgi edinme, yetenek ve yaratıcılıklarını geliştirme gibi olumlu sonuçlarından da faydalandıkları söylenebilir.…”
unclassified
“…But cyberloafing is different from classic versions of counterproductive behavior, such as theft at work, sexual harassment, deliberate delay, etc. It's linked to boredom in the workplace [16] and has positive effects such as minimizing stress, improving mood [17] and self-education [18].…”
Section: Theoretical Background 21 Cyberloafingmentioning
confidence: 99%
“…The concept of cyberloafing was first created by Tony Cummins in 1995 with the combination of 'cyber' that means 'virtual' and 'loafing' that means 'slacking' and became widespread after Lim's (2002) study. In the international literature, the concept has been entitled as cyberloafing (Lim, 2002;Saleh et al, 2018), cyberslacking (Block, 2001;Vitak et al, 2011), and cyberdeviancy (Weatherbee, 2010).…”
Section: Cyberloafingmentioning
confidence: 99%